Validation of the translated Negative Physical Self Scale in a female North American sample: Preliminary examination. (August 2019) - Ly, May; Misener, Kaylee; Libben, Maya
Abstract: In an increasingly multicultural society, there is a need for cross-cultural research on measures of body dissatisfaction, a construct often influenced by sociocultural differences. The current study assessed the psychometric properties of an English translation of the Negative Physical Self Scale (NPSS; Chen, Jackson, & Huang, 2006). A sample of 646 young adult North American women completed an online survey including the NPSS and two widely used measures of body image and eating concerns. Exploratory factor analysis revealed a four-factor structure of the NPSS, three of which (Thinness, Shortness, and Facial Appearance) mirrored those found in Chinese samples. The remaining factor, labeled the Body Concern subscale, was an amalgamation of two factors found in Chinese samples, Fatness and General Appearance, and one item from the Facial Appearance subscale. Extracted factors had high internal consistencies (Cronbach's alpha values above 0.89). The NPSS, particularly the Body Concern Subscale, demonstrated strong convergent validity with other measures of body dissatisfaction and disordered eating. The current study provided evidence for the use of a four-factor model of the NPSS among a North American population. Highlights: Psychometric properties of the English-translated NPSS were investigated. A four-factor model emerged from the English-translated NPSS. The NPSS demonstrated strong convergent validity with the BSQ and EDE-Q. Resulting factor structures may be due to sociocultural body image differences.